A perspective on the commercial viability of perovskite solar cells - JinKiong, Ling; Pradeep, Kumar; Kizhakkedath, Koyadan; Watson, Trystan M.; Mora-Sero, Ivan; Schmidt-Mende, Lukas; Brown, Thomas M.; Rajan, Jose (John Wiley and Sons, 2021)
Perovskite solar cells (PSCs) have received a large amount of research funds due to their potential as a frontrunner in a new generation of solar cells; consequently, the desire to commercialize this technology is mounting. In this roadmap, the knowledge and the technological gaps between laboratory and industry are critically analyzed from the perspective of 5S criteria (Stability, Safety, Sustainability, Scalability, and Storage). To avoid any favoritism in the arguments toward commercializing this technology, herein, the average parameters of PSCs (photoconversion efficiency, durability, cost, manufacturability, and sustainability) estimated from previous studies are analyzed and discussed. Unique opportunities for PSCs in their current stage of achievements are identified, where application-driven, instead of performance-driven, developments are shown to favor their commercialization. Efforts required to improve the average performance of PSCs to state-of-the-art levels are also identified and discussed.